The principles of social teaching of the catholic church (The Journal of Psychology and Sociology, 2015)
The article studied the principles of the social teaching of the Catholic Church: the dignity of the human person, the common good, subsidiarity and solidarity. This study makes possible in no small part to understand contemporary social doctrine of the Church, and in the future, studying specific questions to understand it´s position and the basis for the argu ment.
Keywords: social teaching; Catholic Church; the principle of human dignity; the common good; the universal destination of goods; subsidiar it; participation; solidarity.